Experience of an internationalization strategy in Nursing graduate programs: Cultural and learning exchange - Briñez Ariza, Karol Johanna (2021)
Internationalization strategies in graduate nursing programs are designed and implemented as responses to policies and curricula based on the quality of academic training. This article aimed to describe the experience of implementing an internationalization strategy in nursing graduate programs with the participation of students from Colombia, Mexico and Nicaragua. It was developed through the projection of a novel proposal that did not generate economic investment on the part of the students enrolled in the Master's and Doctorate graduate programs. As conclusions, the need to recognize in the changes in the development of postgraduate subjects such as, for example, the use of other modalities of encounter with the use of information technologies and communication between people from different geographical locations, communication with international nursing graduate programs, the creation of scientific events with nursing graduate students from different countries an opportunity for improvement that dialogue with global and national policies of internationalization in graduate programs that promote cultural exchange and learning between people who do not know each other through an interesting concept: the process of exchanging ideas, thoughts of knowledge, culture, research approaches. Given that the students of the nursing postgraduate programs respond to new ideas and strategies that contribute to their academic training with benefits such as: not generating an additional economic investment, accessibility, remote connection for meetings and thus, potentiate learning in the topics who are passionate about, in our case, qualitative research in nursing.